2012
DOI: 10.1177/1420326x12465764
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Numerical Simulation with Fungal Spore Deposition and Subsequent Fungal Growth on Bathroom Wall Surface

Abstract: Fungal contaminations in indoor environment are recognized as one of the serious problem in terms of health and aesthetic impact. Large numbers of studies have shown an association between the health risk of fungal contamination. Residence in houses and fungal growth is well known to be strongly related to various indoor environmental parameters and hence the development of a comprehensive prediction method for fungal contamination is needed for healthy indoor environmental design. This research focused on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This hot water would produce temperature and humidity differences between the floor and ambient air, causing buoyancy effects to occur and making variation in the water vapour and air temperature. Ito 8 reported that the buoyancy effects caused by the humidity differences are small compared to the buoyancy effects caused by the temperature difference. Droplets would be generated during a shower in general.…”
Section: Boundary Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hot water would produce temperature and humidity differences between the floor and ambient air, causing buoyancy effects to occur and making variation in the water vapour and air temperature. Ito 8 reported that the buoyancy effects caused by the humidity differences are small compared to the buoyancy effects caused by the temperature difference. Droplets would be generated during a shower in general.…”
Section: Boundary Conditionmentioning
confidence: 99%
“…[4][5][6][7] On the other hand, there have only been a very small number of research studies aimed at improving the ventilation performance of the bathroom and its IEQ. Ito 8 proposed an analysis model that can predict fungal contaminants and fungal growth problems in a bathroom. Tung et al 9 examined experimentally the effects of the toilet location and ventilation rate on the ventilation efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, problems emphasising biological diffusion are frequently studied or solved based on examples of animal movement (Benhamou 2014), diffusion of plants or seeds (Coulson et al 2014) and spores (Ito 2013). However, there are situations in which spreading particles are not living organisms, despite being associated with them.…”
Section: Introductionmentioning
confidence: 99%